Clustering Research on Sukuk-Waqf - Aam Slamet Rusydiana; Mohammad Mahbubi Ali (International Journal of Waqf, 2023)
This research aims to look at the development of "Sukuk-Waqf" research throughout the world and research map that can be carried out based on journals published on this theme. This research uses qualitative methods with a bibliometric analysis approach. The data used is secondary data with the theme Sukuk-Waqf which comes from the Dimension database with a total of 133 journal articles. Then, the data is processed and analyzed using the VosViewer application with the aim of knowing the blibliometric map of Sukuk-Waqf research development in the world. The results of the research found that in bibliometric author mapping the authors who published the most research on the theme Sukuk-Waqf were Musari, Khairunnisa; Umam, Khoirul; Tanjung, Hendri; Muneeza, Aishath; Haneef, Mohamed Aslam; Hosen, Muhamad Nadratuzzaman; Aqbar, Khaerul; Afrianti, Wahyuni; Wahab, Abdul; Wahyuni, Sri; Mukhlisin, Murniati; and Rodoni, Ahmad. Furthermore, based on bibliometric keyword mapping, there are 4 clusters that can become research paths with topics related to (1)Economic Development through Waqf Management and Sukuk Waqf, (2)Impact of the COVID-19 Pandemic on the Economy and Sukuk Waqf, (3)SDGs and Sukuk Waqf, and (4)Cash Waqf Linked Sukuk. Furthermore, the words most used are Sukuk, CWLS, covid, sukuk waqf, investor, and economy.